Etnomatematika: Nilai dan Konsep Matematika pada Benda Bersejarah di Museum Airlangga Kota Kediri - Ardilla, Hellen Putri Octa; Gusniawati, Ayu; Jatmiko, Jatmiko (Universitas Ma'arif Lampung, 2025)
Ethnomathematics is an approach that connects mathematics and culture. This study aims to describe the mathematical concepts contained in historical objects in the Airlangga Museum, Kediri City. This research uses a descriptive qualitative approach with observation, interview, and documentation methods. Data were collected through direct observation of historical objects, interviews with museum staff, and photo documentation. The results showed that historical objects in Airlangga Museum Kediri City, such as year number stones, ceke'r inscriptions, and stone barrels, contain mathematical concepts. This shows that mathematics has been integrated in the culture and life of the people of Kediri since ancient times. This research is expected to be an inspiration for the development of meaningful and cultured mathematics learning